Can pulse wave velocity measured preoperatively predict hypotension in hypertensive patients during anesthesia induction? - Sinan Yılmaz; Imran Kurt Ömürlü (Annals of Saudi Medicine)
BACKGROUND: During the induction of general anesthesia, hemodynamic instability is a common occurrence in elderly hypertensive patients with increased arterial stiffness, which can cause undesirable complications. Pulse wave velocity (PWV) is an important indicator of arterial stiffness. OBJECTIVES: Investigate if preoperatively measured PWV is related to hemodynamic changes during induction of general anesthesia. DESIGN: Prospective, case control. SETTING: University hospital. PATIENTS AND METHODS: The study was carried out between December 2018 and December 2019 in patients 50 years or older scheduled for elective otolaryngology with endotracheal intubation and who had an American Society of Anesthesiologists (ASA) score of I or II. Patients diagnosed with hypertension (HT) or receiving treatment for hypertension for systolic blood pressure (SBP) ≥140 mm Hg and/or diastolic blood pressure ≥90 mm Hg were compared with non-hypertensive patients (non-HT) of matching age and gender. MAIN OUTCOME MEASURES: PWV values between HT and non-HT patients and hypotension rates at the 30th second of induction, the 30th second of intubation, and the 90th second of intubation between the HT and non-HT groups. SAMPLE SIZE: 139 (95 with HT and 44 non-HT) RESULTS: PWV was higher in the HT group than in the non-HT group (P<.001). Hypotension at the 30th second of intubation in the HT group was significantly more frequent than in the non-HT group (P=.025). PWV was higher in hypotensive (n=62) than in non-hypotensive patients but the difference was statistically significant only for PWV measured at 30th second of intubation (n=77) (P=.018). CONCLUSIONS: The easily and non-invasively measured preoperative PWV may be an effective means of predicting hypotension during the induction of general anesthesia at the 30th second of intubation in HT patients. LIMITATIONS: Numbers of patients in the groups were not the same, and the study was not sufficiently powered to investigate the effect of hypertensive medications on PWV and arterial stiffness. CONFLICT OF INTEREST: None.